FRET controlled photoluminescence in β-In2S3 microflower—Au nanoparticle ensemble. (17th June 2016) - Warrier, Anita R; Parameswaran, Chithra; Bingi, Jayachandra; Vijayan, C
Abstract: We report on the exciton–plasmon interaction and fluorescence resonance energy transfer controlled photoluminescence quenching and switching in β -In2 S3 microflowers dispersed in Au nanoparticle colloid. The strong resonant interaction of excited β -In2 S3 microflowers with the surface plasmons of Au nanoparticles (∼520 nm) lead to shift in the excitonic binding energy (2.4 eV) with a magnitude of ∼50 meV. In the proximity of Au nanoparticles, the broad emission spectrum of β -In2 S3 microflowers with prominent peak at wavelength of ∼540 nm is quenched and the peak switches to wavelength of ∼600 nm. We demonstrate that the quenching and switching of emission band depends on the rate of fluorescence resonance energy transfer, extent of spectral overlap and β -In2 S3 microflowers (donor)- Au nanoparticles (acceptor) distance. This study opens the wide possibility of fabricating sensors and photonic devices with tunable optical properties.